Online Matchmaking
XIV, 209 p.
Keywords: Online Matchmaking examines the joys, fears, and disappointments of hooking up with people in cyberspace. Unlike many other books in the field, this collection includes studies by experts from a range of disciplines including Communications, Cultural Studies, Health, Journalism, Psychology, Rhetoric, and Sociology.